A Discrete, Linear Input - Output Model of Chaukhutia Watershed For Estimation of Suspended Sediment Flow - R.A.S Patel (Journal of Soil and Water Conservation, 2022)
The erosion of the land surface and its deposition in the river beds and reservoirs are the main factor for reducing its capacity resulting in flood hazards. Further erosion of topsoil adversely affects the productivity of the cropped land. Therefore, the study of the suspended sediment flow in the catchment area needs to be carried out for design, development and estimation of the life span of the reservoirs. The suspended sediment loads in a stream are the result of processes of erosion and transportation within the drainage basin area. The rainfall-sediment yield process is highly complex in nature; therefore linear theory is frequently used because of its simplification. In this study watershed fluvial system is considered as a lumped linear time invariant system based on input- output approach. Chaukhutia watershed of Ramganga catchment is selected for study the sediment flow using the input data of mobilized sediment (similar to rainfall- excess in runoff studies) and output data of direct sediment discharge.